Complete genome sequence analysis of a novel alkane-degrading bacterial strain, Acinetobacter vivianii KJ-1, and its diesel degradation ability - Zhang, Yali; Song, Fanyong; Wang, Jianing; Zhao, Qingqing; Zheng, Liwen; Wang, Zhenjie; Zhang, Xinjian; Gao, Yongchao; Chen, Guanhong; Huang, Yujie (Frontiers in Environmental Science, 2022)
With the increasing demand for diesel in various countries, the ecological pollution caused by the improper use, storage, and accidental leakage of diesel needs to be addressed urgently. As an environmentally friendly and cost-effective method, bioremediation generally uses various microorganisms to remove pollutants from the environment. Here, the strain KJ-1, obtained through an enrichment culture using n-dodecane from oil-contaminated soil near a gas station as the substrate, was identified as Acinetobacter vivianii according to its morphology, biochemistry, and molecular biology. The isolate KJ-1 was able to use diesel as a sole carbon source and more than 40% of diesel was degraded after 12 days of incubation with strain KJ-1 in mineral salts medium. The most suitable diesel concentration and nitrogen source concentrations were 4,140 mg/L and 350–700 mg/L, respectively, for diesel degradation and bacterial growth. The optimal initial pH and temperature for strain KJ-1 growth and diesel degradation were 6.5–8.0 and 20–37°C, respectively. To investigate the diesel-degrading mechanisms of this strain, the complete genome was sequenced and annotated. The complete genome consists of one chromosome with a total length of 3,927,757 base pairs and a G + C content of 41.5%. The genes related to the two-component regulatory system and alkane degradation were analyzed. In addition, two putative alkane monooxygenases were analyzed, and the protein sequences were characterized and compared with other AlkBs in Acinetobacter spp. using sequences downloaded from NCBI. The results demonstrated that A. vivianii KJ-1 may be particularly useful for future bioremediation of diesel-polluted soil.